Student Perception of ESP Business English Teaching Implementation in Makassar National Informatics Polytechnic - Rahmi Rahmi; Abduh Abduh; M. Sofyan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
English for Specific Purpose (ESP) is currently a subject that must be followed by every student in every vocational or polytechnic tertiary institution throughout Indonesia, including in South Sulawesi. This study aims to find out in advance the students' perceptions of English for Specific Purpose (ESP) Business English teaching materials, and their perceptions of the teaching strategies adopted by ESP Business English teachers. In answering the research questions above, researchers used a descriptive qualitative approach. The method of data collection is done through semi-structured interviews using open-ended questions and analyzing them using an interpretative analysis approach. From the results of data analysis found 1) the material or textbooks that are used already meet the learning needs of students where the materials provided include Business English related words, the structure of Language/Grammar, and practical language teaching. However, students consider the design or appearance of the book to be less attractive making them less interested in using the book; 2) students show a variety of perceptions about the teaching strategies of their lecturers, found themes that show the teaching strategies preferred by students are supportive, create fun learning, provide games, be disciplined and assertive but feel not pressured, have an active professional knowledge component.